On Infinitesimal Projective Transformations of the Tangent Bendle With the Complete Lift of A Finsler Metric - Bidabad, Behroz; MirMorhamad Rezaii, Morteza; Zohrehvand, Mosayeb (IndoMS, 2017)
Let (M,g) be a Finsler manifold and TM0 its slit tangent bundle with the complete lift metric g.In this paper we prove that every infinitesimal complete lift projective transformation on (TM0, g), is an infinitesimal affine transformation. Moreover, if (M,g) is a Landsberg manifold, then there is a one-to-one correspondence between infinitesimal complete lift projective transformations on (TM0, g) and infinitesimal affine transformations on (M,g).